The Price of Extinction and the Epic Journey to Mourn Beyond the Human in Ned Beauman’s Venomous Lumpsucker - Torres Romero, María (Lagoonscapes)
This article aims to explore how contemporary speculative fiction contributes to the current debate about the extinction crisis in the context of the Anthropocene by the critical analysis of Ned Beauman’s latest novel Venomous Lumpsucker (2022). First, it explores how in a future speculative world, where the exploitative drive of the neoliberal economic system interlocks with the latest technologies, the monetisation of life ends up detaching the notions of extinction and death. Additionally, it follows and interprets the epic travel of a cognitive scientist from apathy to environmental awareness and her complex journey towards mourning beyond the human.